Ethical challenges in mental health research with focus in Nepal - Khanal, Pratik; Maharjan, Sajana (Health Prospect, 2018)
People with mental health problems are considered as vulnerable population by national ethical guidelines of health research in Nepal. There are different ethical challenges in research involving people with mental health problems. Ethical challenges are related to study design, autonomy, beneficence and nonmaleficence, justice, respect for the environment and consent taking process. Respecting the human rights of those with mental health problems is necessary during research and this requires research stakeholders to be responsible.